Pathogenic SCN2A variants cause early-stage dysfunction in patient-derived neurons - Asadollahi, Reza; Delvendahl,; Muff, R.; Tan, G.; Rodrieguez, D. G.; Turan, Sören; Russo, M.; Oneda, B.; Joset, P.; Boonsawat, P.; Masood, R.; Mocera, M.; et al. (Human Molecular Genetics, 2023)
Pathogenic heterozygous variants in SCN2A, which encodes the neuronal sodium channel Na(V)1.2, cause different types of epilepsy or intellectual disability (ID)/autism without seizures. Previous studies using mouse models or heterologous systems suggest that Na(V)1.2 channel gain-of-function typically causes epilepsy, whereas loss-of-function leads to ID/autism. How altered channel biophysics translate into patient neurons remains unknown. Here, we investigated iPSC-derived early-stage cortical neurons from ID patients harboring diverse pathogenic SCN2A variants [p.(Leu611Valfs*35); p.(Arg937Cys); p.(Trp1716*)] and compared them with neurons from an epileptic encephalopathy (EE) patient [p.(Glu1803Gly)] and controls. ID neurons consistently expressed lower Na(V)1.2 protein levels. In neurons with the frameshift variant, Na(V)1.2 mRNA and protein levels were reduced by similar to 50%, suggesting nonsense-mediated decay and haploinsufficiency. In other ID neurons, only protein levels were reduced implying Na(V)1.2 instability. Electrophysiological analysis revealed decreased sodium current density and impaired action potential (AP) firing in ID neurons, consistent with reduced Na(V)1.2 levels. In contrast, epilepsy neurons displayed no change in Na(V)1.2 levels or sodium current density, but impaired sodium channel inactivation. Single-cell transcriptomics identified dysregulation of distinct molecular pathways including inhibition of oxidative phosphorylation in neurons with SCN2A haploinsufficiency and activation of calcium signaling and neurotransmission in epilepsy neurons. Together, our patient iPSC-derived neurons reveal characteristic sodium channel dysfunction consistent with biophysical changes previously observed in heterologous systems. Additionally, our model links the channel dysfunction in ID to reduced Na(V)1.2 levels and uncovers impaired AP firing in early-stage neurons. The altered molecular pathways may reflect a homeostatic response to Na(V)1.2 dysfunction and can guide further investigations.
CRIS-Team WoS Importer:2023-05-26